Pola Komunikasi Organisasi Dalam Meningkatkan Efektifitas Program Kerja Di Futsal Ekonomi Singaperbangsa Karawang - Bagas Mahaputra Irawan; Aa Ahmad Fauji; Dian Hakip Nurdiansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Etymologically, the word communication comes from the Latin "communicare" which means "to convey". According to the origin of the word, the meaning of communication is the process of conveying meaning from one entity or group to another through the use of signs, symbols and semiotic rules that are understood together. This journal was compiled using a qualitative method, in which the researcher uses a data collection process to provide an overview of the social phenomena being studied. By using qualitative data, researchers can find out why, what and how social phenomena occur. Based on the results of the research, the researchers suggest that the management of Economic Futsal 2021 will run well because there is no work program that makes Economic Futsal effective.